Biobridge: An Outlook on Translational Bioinks for 3D Bioprinting (Adv. Sci. 3/2022). Issue 3 (25th January 2022) - Gu, Yawei; Forget, Aurelien; Shastri, V. Prasad
Abstract : Translational Bioinks for 3D Bioprinting 3D‐Bioprinting, a technology at the interface of additive manufacturing, biomaterials and cell biology, is poised to revolutionize regenerative medicine and drug screening. Bioinks are the lynchpin as they bridge bench to bedside. A biology‐based approach to engineering bioinks with pro‐regenerative attributes, with an emphasis on reproducibility, efficiency, and conformance to regulatory standards is essential for paving the way to clinical translation. More details can be found in article number 2103469 by V. Prasad Shastri and co‐workers.